Evaluation of State Bank Performance Based on The Regulation of Bank Indonesia Number: 13/1/PBI/2011 (A Study on State Bank of Indonesian Government in 2018) - Irtriani, Vike (Jurnal Ilmiah Mahasiswa FEB, 2020)
This study aims to evaluate the soundness level of State Bank of Indonesian Government under Bank Indonesia Regulation No. 13/1/PBI/2011 about Banks Financial Health Assessment using Risk Based Bank Rating (RBBR) approach with measuring the Risk Profile, Good Corporate Governance, Earnings, and Capital factors. This is a descriptive study with quantitative approach. The population of this study was State Banks of Indonesian Government. The sample of this study was BNI, BRI, Bank Mandiri, and BTN. The data used was secondary data in the form of annual financial statements and annual reports. The data was processed by Microsoft Excel and analyzed using the descriptive quantitative technique. This study found, in the measurement of Risk Profile factor represented by NPL, IRR, LDR, LAR, and CR ratio at, that BNI, BRI and Bank Mandiri were classified as very healthy while BTN as healthy. The rank of LDR shows, that only BTN was categorized not ideal. The assessment of 11 aspects of Good Corporate Governance at Bank Mandiri were categorized as very healthy while BNI, BRI, and BTN were in the healthy category. The measurement of Earnings factor using ROA and NIM ratio, and Capital factor using CAR ratio showed that BNI, BRI, Bank Mandiri, and BTN were in the very healthy category. Accordingly, State Banks of Indonesian Government in 2018 have an excellent condition in overall, so they will be able to overcome the liabilities issue. Keywords: Bank Soundness, Risk Based Bank Rating, RGEC method, State Banks of Indonesian Government (Banks of SOE)